Caustic ingestion injuries: evaluation of 108 cases - Ali Önder KARAOĞLU; Ömer ÖZÜTEMİZ and Tankut İLTER and Yücel BATUR and Nadir YÖNETÇİ and Oktay TEKEŞİN and; t MUSLUOĞLU and; t AYDIN and; a OSMANOĞLU and; AKARCA and; l. (Turkish Journal of Gastroenterology, 2019)
-